Climate Justice and Environmental Politics: Examining the North-South Divide with a Focus on Pakistan - Muhammad Younas; Dr. Saweeda Rahman (Social Science Review Archives, 2025)
This article critically examines the intersection of environmental politics and climate justice while focusing on Pakistan as a case study from Global South. This study is based on the theoretical lens of Critical Political Ecology (CPE) which reveals that the current global environmental order is unjust and is shaped by historical emissions of the Global North, geopolitical power asymmetries, and epistemic exclusions. The countries in the Global South have minimal contribution to global greenhouse gas emissions (GHGs) but face disproportionate climate risks because of the structural vulnerabilities and systemic inequities. This analysis of this paper reveals that dominant environmental governance models privilege technocratic and market-based solutions while marginalizing the Southern voices. During the 2022 floods and COP27, Pakistan’s experience shows that its vulnerability to environmental impacts provides it with visibility and voice in the international environmental regime within existing institutional constraints. Addressing the current imbalance of environmental costs and benefits is possible through decentralizing environmental governance and addressing underlying power imbalances, socio-political inequalities, and historically rooted injustices.